Characteristics of Antimicrobial Activity of Eucheuma cottonii Doty-Associated Bacteria Extracts - Risa Nofiani; . Kadarisno; . Daryati; Ajuk Sapar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2009)
Marine organisms-associated bacteria have a potential source of antimicrobial compounds. The aim of the research was to find out characteristics of antimicrobial activity of E. cottonii Doty-associated bacteria extracts and their genus from Lemukutan Island, Kalimantan Barat. Five of 11 isolates showed antimicrobial activity namely Flavobacterium sp. K08, Alteromonas sp. K09, Bacillus sp. K10, Klebsiella sp. K11, and Pseudomonas sp. K12. Furthermore, their secondary metabolites were extracted with methanol. The characteristic of the best bacteria extracts minimum inhibitory concentrations (MICs) for Escherichia coli, Bacillus spaericus, Staphylococcus epidermidis, and Candida tropicalis were obtained from bacteria extract of Bacillus sp. K10 (250 μg/disc), Bacillus sp. K10 (750 μg/disc), Pseudomonas sp. K12, (500 μg/disc), and Alteromonas sp. K09 (1,500 μg/disc) respectively.Keywords: antimicrobial activity, Alteromonas sp., E. cottonii Doty, Flavobacterium sp., Pseudomonas sp.